The use of digital technology in health learning during the COVID-19 pandemic: a systematic review - Soares, Domingos; Nursalam (Journal of the Pakistan Medical Association, 2023)
Objective: To investigate reasons, advantages, disadvantages and obstacles in the use of digital technology media for health learning during the coronavirus disease-2019 pandemic. Methods: The systematic review was conducted from January to February 2022 and comprised search on Google Scholar, ProQuest, PubMed, ScienceDirect and Scopus databases for articles published from 2020 to March 2022 related to the use of digital technology by medical students, teachers and academics. Key words used for the search included digital technology, health learning, health education, COVID-19, COVID-19 pandemic, and coronavirus disease 2019. Main themes were identified which were then grouped into components using Joanna Briggs Institute guidelines and tools. Results: Of the 128 articles initially found, 10(7.8%) were subjected to detailed analysis. Reasons identified were lockdown and accessibility of flexible learning materials. Advantages were effective time, better effort, saving money, improving technical skills, health security, feasibility, e-learning standardising, dedicated teaching, interdisciplinary collaboration network, creativity, inclusivity and professional development. Disadvantages were inadequate tools, poor internet connection, lack of technical skills, practical in classes, unclear policies, examinations, distribution of grades and limited online exam time. Obstacles included virtual class etiquette disobedience, inadequate interactions, time limitations, infrastructure, distractions, lack of engagement, stress, technical and limited data plans. Conclusion: Many universities used digital technology in health learning during the pandemic-led lockdowns as it provided greater advantages. Keywords: COVID-19, Digital Technology, Pandemics, Communicable disease control.